From prosecutorial supervision to public interest protection (Academic Journal of Internal Affairs, 2016)
Focusing on areas outside the scope of criminal law, the author provides an overview of the changing role and competences of the prosecutor in Hungary.
Keywords: prosecutor; changing role; Hungary